The Role of Geomorphological Factor on The Urban Expansion of Both Shaqlawa and Soran cities –A comparative study in Urban Geomorphology - Kamaran Wali Mahmood; Hikmat Abdul-Azez Hamad Al-Husaini (Zanco Journal of Humanity Sciences)
This paper is an investigation into the joint influence of geomorphology and urban geography in urban geomorphology. The importance of the paper stems from the fact that the correctness or incorrectness of the choice in directing the expansion of cities has positive or negative effects and consequences on both the population and the government. Methods, the urban evolution of the two cities, and the results and discussion are the three primary sections of this paper, which aims to determine the extent to which the expansion of the mountain cities of Shaqlawa and Soran takes into account the geomorphological factor. The paper concluded that, in the absence of government involvement, the population's choices have always gone towards the most optimal areas for the safety of buildings and houses, by selecting the Shiranish and Tanjero formations in both cities. Also, due to the impact of tourism investments, geomorphological variables have a part even in irrational choices to move to the heights of the mountains, like in Shaqlawa.